Effects Of Ethnic And Communal Conflicts In Ekoi Tribe: The Experience Of Old Obubra In Cross River State - Egbara Owa, Ph.D, Owa; Ikechukwu Ugwuerua, Ph.D, Emmanuel; Ucha Egwu, Ph.D, Joy; Egbara Owa, M.Sc, Wisdom (International Journal of Psychosocial Rehabilitation, 2020)
The Ekoi tribe of the Cross River State extraction has experienced ethnic and communal conflicts at an endemic proportion, a situation that has plunged the area into underdevelopment. This crisis has often been caused by primordial sentiments. The paper attempted to unravel the remote and immediate causes of the ethnic and communal conflicts in Ekoi-land and their corresponding consequences on the development of the area, with a focus on the old Obubra. Moreso, to proffer solutions through recommendations to curb the menace in order to enable the Ekoi nation to develop to greater heights. Old Obubra of Cross River State comprises of three local government areas, which are: Abi, Obubra, and Yakurr, respectively. Data for the study were elicited through primary and secondary sources. The study discovered that the causes of ethnic and communal conflicts include the quest for political hegemony, land resources—territorial inhabitations, holding claims to aborigine status, and chieftaincy. The theoretical framework that guided the study is the Marxian social conflict theory, with the objectives of exploring the causes and effects of ethnic and communal conflict in Ekoi-land with the view of finding solutions to stem the tide. The study stated both the null (Ho) and alternative (H1), respectively. Ho: Ethnic and communal conflicts have not underdeveloped Ekoi land. H1: Ethnic and communal conflicts have underdeveloped Ekoiland. Recommendations were made to include that the traditional institutions of the Ekoi-tribe should be strengthened to be able to settle issues that border on political power, land, resources, territorial inhabitations, and chieftaincy. There should be the prohibition of ethnic infractions through constitutional review, and enlightened elites should be encouraged to hold traditional positions to be able to contribute their wealth of experience gathered during their service years in their respective careers.